Strategic Planning for Engagement in the #Kuliahtakperlujauh Campaign: Enhancing Higher Education Participation in Brebes Regency – Central Java - Agus Isnaeni; Nani Nurani Muksin (Ikatan Sarjana Komunikasi Indonesia, 2026)
This article investigates the strategic use of digital engagement in the #Kuliahtakperlujauh campaign, initiated by local higher education institutions in Brebes, Central Java, to address low participation in tertiary education. Rather than focusing solely on outcomes, the study analyzes campaign planning through the dual lens of the AISAS model (Attention, Interest, Search, Action, Share) and Customer Engagement Theory (cognitive, affective, conative dimensions). Data were collected from interviews and focus group discussions with students, parents, and campaign organizers. Findings reveal that platform-specific strategies TikTok for youth attention, Instagram for aspirational storytelling, Facebook for parental credibility, and WhatsApp for reinforcement, were designed to align audience needs with platform affordances. Alumni storytelling and localized visual identity fostered curiosity, pride, and emotional resonance, while dialogic features such as live Q&A sessions enhanced participatory engagement. However, cultural stigma, parental skepticism, and digital inequality presented significant barriers, underscoring the need for hybrid strategies that integrate online communication with offline trust-building. The study contributes theoretically by extending AISAS beyond consumer contexts and integrating it with Customer Engagement Theory, offering a conceptual model for understanding digital engagement in higher education. Practically, it emphasizes that sustainable campaigns in non-metropolitan areas require institutional commitment, community co-ownership, and adaptability to shifting digital cultures. The Brebes case demonstrates how digital engagement can act as a transformative communication strategy to reframe local higher education as accessible, credible, and socially meaningful.